Clinical Characteristics in Patients with Triple Negative Breast Cancer. (17th August 2017) - Yeh, Janet; Chun, Jennifer; Schwartz, Shira; Wang, Annie; Kern, Elizabeth; Guth, Amber A.; Axelrod, Deborah; Shapiro, Richard; Schnabel, Freya
Abstract : Purpose . The purpose of this study was to compare and contrast the clinical characteristics of the triple negative breast cancer (TNBC) and non-TNBC patients, with a particular focus on genetic susceptibility and risk factors prior to diagnosis. Methods . Our institutional database was queried for all patients diagnosed with invasive breast cancer between January 2010 and May 2016. Results . Out of a total of 1964 patients, 190 (10%) patients had TNBC. The median age for both TNBC and non-TNBC was 59 years. There was a significantly higher proportion of African American and Asian patients with TNBC (p = 0.0003 ) compared to patients with non-TNBC. BRCA1 and BRCA2 were significantly associated with TNBC (p < 0.0001, p = 0.0007 ). A prior history of breast cancer was significantly associated with TNBC (p = 0.0003 ). There was no relationship observed between TNBC and a history of chemoprevention or patients who had a history of AH or LCIS. Conclusions . We found that having Asian ancestry, a prior history of breast cancer, and a BRCA1 or BRCA2 mutation all appear to be positively associated with TNBC. In order to develop more effective treatments, better surveillance, and improved prevention strategies, it is necessary to improve our understanding of the population at risk for TNBC.